Pengaruh Stres Kerja terhadap Kepuasan Kerja Karyawan dengan Dukungan Sosial sebagai Variabel Moderasi - Sanjaya, Bagus (Jurnal Ilmu Manajemen, 2021)
This research aims to examine and analyze the impact of work stress on job satisfaction with social support as a moderating variable. This research method is quantitative, using Simple Random Sampling for its sampling technique. There were 60 employees as samples—the data collected by observation, interviews, and questionnaires. The statistical analysis used in this study was descriptive analysis and data analysis by utilizing Partial Least Square (PLS) with SmartPLS 3.0 as the tool and Statistical Package for the Social Science (SPSS) software. The result shows that work stress has a negative and significant influence on job satisfaction. Work stress will result in a decrease in job satisfaction felt by employees. As well as social support did not moderate the relationship between work stress and job satisfaction. Social support does not decrease the impact of work stress on job satisfaction that occur within the company. The company should manage the work stress level to fulfil workers' job satisfaction and avert adverse effects to the company's activities.